THE INFLUENCE OF APPARATUS COMPETENCE, INTERNAL CONTROL, AND WHISTLEBLOWING ON THE PREVENTION OF FRAUD IN VILLAGE FUND MANAGEMENT WITH RELIGIOSITY AS A MODERATING VARIABLE - Aimanah, Ummul; Yuliusman, Yuliusman; Ridwan, Muhammad (Universitas Nusa Cendana, 2024)
This study aims to determine the effect of apparatus competence, internal control, and whistleblowing on the prevention of fraud in village fund management, as well as the role of religiosity in moderating apparatus competence, internal control, and whistleblowing. This study uses a quantitative methodology. The Batin XXIV sub-district's village apparatus is included in the study's population. Purposive sampling was the method of sampling employed in this investigation, yielding a sample size of sixty respondents overall. PLS (Partial Least Square) is the data analysis technique used in this study, and SmartPLS software version 4.0.9.6 was used to process the data. The results of this study indicate that apparatus competence, internal control, and whistleblowing have a positive and significant effect on the prevention of fraud in village fund management. Religiosity does not moderate the relationship between apparatus competence and the prevention of fraud in village fund management, nor does it moderate the relationship between internal control and the prevention of fraud in village fund management. However, religiosity can moderate the relationship between whistleblowing and the prevention of fraud in village fund management. Keywords: Apparatus Competence; Internal Control; Whistleblowing; Religiosity; Fraud Prevention